Colistin-associated Stevens-Johnson syndrome and toxic epidermal necrolysis reactions: a retrospective case-non-case pharmacovigilance study. Issue 8 (3rd August 2022) - Tang, Richard; Lopes, Vrishali L.; Caffrey, Aisling R.
ABSTRACT: Background: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are life-threatening skin reactions. Colistin is a last resort antibiotic with a historically poor safety profile. The association between colistin and SJS/TEN has not been previously quantified. Research design and methods: We identified colistin and SJS/TEN adverse event reports from the Food and Drug Administration Adverse Event Reporting System (FAERS) and calculated effect estimates using OpenEpi. Results: From January 2013 through March 2021, 964 adverse events were reported for colistin. Colistin was listed as a secondary suspect drug in 13 SJS/TEN adverse event reports (1.3%), with a reporting odds ratio of 29.6 (95% confidence interval [CI] 17.1–51.1), and proportional reporting ratio of 29.2 (95% CI 17.0–50.2). Limitations of any FAERS study include the voluntary nature of reporting, unclear causal relationship between drug and adverse reaction, underreporting, and wide confidence intervals for rare adverse events like SJS/TEN. Conclusions: Colistin was not the primary suspect drug in any SJS/TEN adverse event reports. We did identify a statistically significant safety signal for SJS/TEN with colistin as a secondary suspect drug. SJS/TEN is not currently included in the colistin product label. This association should be further explored in other pharmacoepidemiologic drug safety studies.